ANALISIS KESESUAIAN PENGGUNAAN LAHAN BERDASARKAN KEMAMPUAN LAHAN DI DAS WAE BATU MERAH KOTA AMBON - Frank Samelino Tita; Bertila Avila Delvion; Fredrik Theodorus Tita (PT. BARRINGTONIA ASIATICA LESTARI, 2024)
The Wae Batu Merah Watershed is one of the micro watersheds in the City of Ambon and is a priority watershed in the Maluku Province. There are indications of land-use incompatibility with the physical capacity of the land (land capability) in this watershed. The objective of this study is to determine the land capability directions and their suitability for current land use in the Wae Batu Merah Watershed. The analysis methods used are the overlay method and the matching method based on the components of land composition and land use suitability. The Wae Batu Merah Watershed has 7 classes of land capability, class II (3.09%), class III (9.39%), class IV (14.17%), class V (18.92%), class VI (13.83%), class VII (32.47%), and class VIII (8.03%). There is an incompatibility of actual land use in the Wae Batu Merah Watershed with the land capability classes: the positively unsuitable category has an area of 148.19 ha or 22.19%, and the negatively unsuitable category has an area of 241.98 ha or 36.24%. The land capability of the Wae Batu Merah Watershed is dominated by land capability classes VI, VII, and VIII, so the recommended land use direction is predominantly conservation or protected areas.